Founder BRCA1/BRCA2/PALB2 pathogenic variants in French-Canadian breast cancer cases and controls - Supriya Behl (Nature Portfolio, 2020)
Abstract Inherited germline pathogenic variants are responsible for ~5% of breast cancer globally. Through rapid expansion and isolation since immigration in the early 17th century, French Canadians are a relatively genetically homogenous founder population and therefore represent a unique demographic for genetic contributions to disease. To date, twenty variants in BRCA1, BRCA2, and PALB2 that predispose families to breast and ovarian cancer have been identified as recurring in the French-Canadian founder population. Our objective was to evaluate the clinical efficacy and validity of targeted genetic testing for these variants in Montreal French Canadians. A total of 555 breast cancer cases unselected for family history or age of diagnosis were genotyped, along with 1940 controls without a personal or family history of cancer. A Sequenom genotyping assay identified a pathogenic variant in 0.2% (5 of 1940) of cancer-free controls, and 3.8% (21/555) of breast cancer cases. Almost 10% (12/113) of early onset cases were heterozygous for founder BRCA1 or BRCA2 pathogenic variant. Of twenty variants tested, only seven were identified in this study. The option of providing this test as population-based screening is discussed.